Dominion or Stewardship? An Ecological Perspective on Genesis 1-2. (Hekima Review, 2010)
Basing its arguments on the biblical accounts of creation found in the first two chapters of the book of Genesis, this paper tries to demonstrate that the Judeo-Christian Creation tradition is or was wrongly accused of being the basis of excessive and harmful exploitation of the planet by granting superiority and power to human beings over other creatures. In making human beings pinnacle of creation, God also entrusts the care of his creation to them. In a sense, human dignity gives them more responsibility. Should we then see only dominion over creation? Or there is also a clear responsibility of human beings for creation? This article points out that a coherent interpretation of the biblical creation narratives would lead to a pro-ecological attitude whereby humans would care for the environment as God’s garden.